Ukraine's western border: risks and potential threats to national security - Dvornichenko, Darina Yu.; Дворниченко, Дарина Юрьевна; Дворніченко, Дарина Юріївна (Одеса, 2016)
У статті аналізуються передумови виникнення та тенденції розвитку викликів безпеці України. Особливу увагу приділено аналізу політичної та дипломатичної боротьби навколо західного кордону України. Визначені ключові осередки потенційної напруги у відносинах України з її західними сусідами.

В статье анализируются предпосылки возникновения и тенденции развития вызовов безопасности Украины. Особое внимание уделено анализу политической и дипломатической борьбы вокруг западной границы Украины. Определены ключевые очаги потенциальной напряженности в отношениях Украины с ее западными соседями.

The article analyzes the prerequisites of emergence and trends in development of Ukraine’s security challenges. Particular attention is paid to the analysis of the political and diplomatic struggle overUkraine’swestern border. Key imbroglios in the relations between Ukraine and its western neighbors are identified.
Dvornichenko D. Yu. Ukraine's western border: risks and potential threats to national security / D. Yu. Dvornichenko // S.P.A.C.E. Society, Politics, Administration in Central Europe : електронний науково-практичний журнал / редкол.: Д. В. Яковлев (голов. ред.), К. М. Вітман (заст. голов. ред.), Д. Ю. Дворніченко (відп. секр.) [та ін.] ; НУ «ОЮА». – Одеса, 2016. – Вип. 1. – С. 72-75.
Keywords: безпека; потенційні загрози; територіальна цілісність; територіальні претензії; західні сусіди України; безопасность; потенциальные угрозы; территориальная целостность; территориальные претензии; западные соседи Украины; security; potential threats; territorial integrity; territorial claims; Ukraine’s western neighbors